Perencanaan Arsitektur Sistem Informasi Pelayanan Kesejahteraan Sosial Menggunakan EAP: Studi Kasus: Dinas Sosial Kabupaten Garut - Topan Setiawan; Miki Wijana; Muhamad Fauzi Fadilah (Jurnal Accounting Information System (AIMS), 2022)
Dinas Sosial Kabupaten Garut is currently still experiencing difficulties in managing information related to social welfare services, so it is necessary to strive for better information management, one form of implementation is by implementing a computer-based information system and technology. In information technology there are three interconnected parts, namely: hardware, software, and databases. Planning an integrated information system architecture and in accordance with the organization's business goals is one of the efforts to improve services in a better direction so that they can compete with other organizations. This study discusses the architectural planning of social welfare service information systems using Enterprise Architecuter Planning (EAP) which was developed and integrated with The Open Group Architecture Framework (TOGAF at Dinas Sosial Kabupaten Garut, where the discussion is focused on four stages, namely: business architecture planning, data architecture planning, application architecture planning, and technology architecture planning. The results of the research that has been carried out are recommendations for the development of information system architecture to support the improvement of public service performance and system integration into all parts of the organization.